Shear Behavior Simulation of Reinforced Concrete Beam Incorporating Glass Fibber-Reinforced Polymer Shear Reinforcement - Rahmat D. Sutrisno; Wahyuniarsih Sutrisno; Harun Alrasyid; Bambang Piscesa; Mudji Irmawan (Institut Teknologi Sepuluh Nopember (ITS), 2024)
This paper presents the shear behavior of concrete beams incorporating glass fiber-reinforced polymer (GFRP) stirrups using a nonlinear finite element simulation package, 3D-NLFEA. The experimental data was adopted from the test results performed by previous researchers. The constitutive model for the concrete material used in this simulation is based on the plasticity-fracture model and considers the tension-stiffening effect of the concrete. The numerical simulation result was compared with the experimental test, including the ultimate shear forcedeflection response and cracking pattern. Based on the analysis result, it was found that the ultimate shear force-deflection response shows almost the same. For the mean ratio of prediction ultimate shear load to actual ultimate shear load from the experimental result and a coefficient of variation of 1.000 and 0.206%, respectively, and deformation results, the mean ratio of prediction deformations for the mid-shear span and mid-span of 0.966 and 0.941, respectively, with the coefficient of variation for the mid shear span and mid-span of 11.849% and 7.627%, respectively. However, the cracking pattern mode of the beam shows good results, which complies with the experimental test.